Pengembangan Video Pembelajaran Terintegrasi Nilai-Nilai Islami terhadap Kemampuan Representasi Matematis Siswa pada Materi Statistika - Nurpintia, Ira; Astuti, Reni; Jamilah, Jamilah (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
This study aims to produce media in the form of learning videos integrated with Islamic values on students' mathematical representation skills on statistics material that reaches the level of validity, practicality, and effectiveness. This research is included in development research using Thiagarajan's 4D research design. The subjects in this study were seventh grade students of Nurul Islam Junior High School Kubu Raya with a total of 22 students. The instruments used in this study were validation sheets, questionnaires, and test questions. Based on the results of the first study, the validation of the learning video is with an average value of the three experts of 90.15% in very valid criteria with very good categories. The second is the value of practicality, seen from the value of the questionnaire filled by teachers and students obtained a percentage of 92% with very practical criteria. Meanwhile, to see the effectiveness of media in the form of learning videos measured from student test results obtained a percentage of 86.36% with very effective criteria. So that the media in the form of learning videos integrated with Islamic values is suitable for use in learning mathematics on statistics material.